Effect of synthetic fibres on fracture performance of asphalt mortar. Issue 7 (2nd October 2020) - Apostolidis, Panos; Liu, Xueyan; Daniel, Gerald C.; Erkens, Sandra; Scarpas, Tom
Abstract : The utilisation of synthetic fibres has been reported in the past showing enhancement of fatigue and thermal cracking resistance in asphaltic materials. However, the limited evidences about the benefits of these fibres in asphaltic materials at low material scales have been noticed. Also, the exact reinforcing mechanism of binding system in the asphalt pavement mixes is still unclear. Therefore, this research examined experimentally the fracture performance of the synthetic reinforced asphalt mixes at the mortar level by using specially designed tools. Samples of three different fibre contents and two fibre lengths were evaluated. Pull-out tests, whose objective was to explore the potential interaction of fibre-matrix, demonstrated a matrix-type of fracture. Moreover, direct tension tests were carried out with both monotonic and cyclic loading to assess the effect of the synthetic fibres on tensile strength, fracture energy and ductility; and fatigue life of reinforced mixes. Improvements on mechanical characteristics of asphalt mortars have been observed when fibres were added. Also, the longer fibres of low dosages generated equivalent performance to the mix with the high dosages of shorter fibre. Hence, a potential initial cost reduction could be reached by means of utilising the longer synthetic fibres. Overall, the current results elucidated that implementing dedicated studies at various material levels can assist on understanding the material performance and on tailoring systems beyond sometimes the supplier-recommended additive dosages.